Causal relationship between Butyricimonas and allergic asthma: a two-sample Mendelian randomization study - Wan, Wei; Qiu, Yi; Huang, Xinyi; Ren, Yingxiang; Peng, Andi; Yang, Chunping (Frontiers in Microbiology, 2023)
Background Growing evidence has well documented the close association between the gut microbiome and allergic respiratory disease, which has been notably represented by allergic asthma. However, it is unclear whether this association is a causal link. Therefore, we investigated the potential causal associations between the gut microbiome and allergic asthma or other allergic diseases. Methods In this study, we performed two-sample Mendelian randomization (MR) analyses by using the publicly available genome-wide association study (GWAS) summary data. Single-nucleotide polymorphisms (SNPs) that significantly correlated were selected as instrumental variables. The inverse variance weighted (IVW) method was used to examine the potential causal gut microbial genera for allergic asthma and other allergic diseases. The robustness of the primary findings of the MR analyses was ensured by using different sensitivity analyses. Results Combining the findings from multiple analyses, the host genetic-driven increases in Butyricimonas at the genus level were positively correlated with the risk of allergic asthma. In addition, phylum Bacteroidetes and class Bacteroidia were also found to have negative associations with the risk of allergic asthma; genus Slackia was identified as having potential causal effects with allergic asthma. No clear evidence of pleiotropy and heterogeneity was observed in genus Butyricimonas. Butyricimonas was also found to have an association with allergic rhinitis, but not with other allergic diseases. Conclusion Our findings indicate that there are new gut microbial genera that were causally associated with the risk of allergic asthma and other allergic diseases, and offer novel insights into the pathogenesis of allergic respiratory diseases.